(In-Vitro Comparison between Closed Versus Open CAD/CAM Systems) Comparison between Closed and Open CAD/CAM Systems by Evaluating the Marginal Fit of Zirconia-Reinforced Lithium Silicate Ceramic Crowns - Gil Ben-Izhack; Asaf Shely; Omer Koton; Avi Meirowitz; Shifra Levartovsky; Eran Dolev (Applied Sciences, 2021)
Background: This study compared the marginal gap (MG) and absolute marginal discrepancy (AMD) of computer-aided design and computer-aided manufacturing (CAD–CAM) used in open systems (OSs) and closed systems (CSs) for producing monolithic zirconia-reinforced lithium silicate (ZLS) ceramic crowns. Methods: 60 ZLS ceramic crowns were cemented to abutment acrylic teeth; thirty crowns were designed and milled by an OS, and thirty by a CS. All crowns were sectioned for evaluating the marginal gap by scanning electronic microscopy (SEM). To compare the marginal gap between CS and OS techniques, data were analyzed using the independent-samples Mann–Whitney U Test (α = 0.05). Results: AMD was found to be significantly better for the closed system (p < 0.05). Mean AMD values for the CS were 148 µm, and for the OS it was 196 µm. MG was found to be significantly better for the OS (p < 0.05). Mean MG values for the CS were 55 µm, and for the OS they were 38 µm. Conclusions: The marginal gap in relation to AMD was significantly better for CS. However, the marginal gap in relation to MG was significantly better for OS. Both techniques showed clinically acceptable MG values (<120 µm).